Pendidikan Agama Islam dan Budi Pekerti - Maemunatun Maemunatun (UM Purwokerto Press, 2023)
Character education has an important role in anticipating future problems, moreover, an educator needs to have the character and attitude of sincerity, sincerity, and amaliyah goals to Allah as exemplified by the Prophet to his friends. The example of sincerity and exemplary has been exemplified by many scholars such as KH. Ahmad Dahlan, Hasyima Asy'ari, and others fought and spent their lives empowering the community. The things that have been exemplified by these figures can be an inspiration to students in schools and Islamic boarding schools to emulate their best so that in the end character education becomes a collective identity. The problems faced by educators must be seen as a collective struggle without expecting praise from others who can erode a sincere attitude towards educating future generations.